PENINGKATAN AKTIVITAS SELULASE PADA TANAH HUTAN MANGROVE PANTAI SUWUNG BALI DENGAN PENGAYAAN SUBTRAT SELULOSA JANUR KELAPA (Cocos nucifera) - Ika Kurniawati; I Nengah Wirajana; I Gede Mahardika (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2013)
The aim of this study is to determine the effect of coconut (Cocos nucifera) leaf enrichment to soil of mangrove forest of Bali Suwung coastal on the cellulase activity. The measurement of cellulase activity was conducted by CMC method (Carboxymethyl Cellulose Assay) on soil sample with and without enrichment of coconut leaf substrate in incubation time of 1, 2, 3, and 4 weeks. The results showed that the enrichment increased cellulase activity. In addition, cellulase activited the soil samples, increase with incubation times.